Karakterisasi dan Pemetaan Profil Fisikokimia Dangke Susu Kuda Liar Khas Nusa Tenggara Barat: Characterization and Mapping of the Physicochemical Properties of Wild Horse Milk Dangke from West Nusa Tenggara - Komalasari, Husnita; Afgani, Chairul Anam; Melandani, Astri (Jurnal Teknologi dan Mutu Pangan, 2025)
Dangke, also known as soft cheese, is a food from Enrekang, South Sulawesi. In the West Nusa Tenggara region, dangke is also widely produced, one of which is made from wild horse milk, which is a local food of NTB. The aim of this research is to determine the characteristics and mapping of the physicochemical profile of dangke of West Nusa Tenggara. The research method used was experimental with a completely randomized design with single factor, namely the type of sample or region of origin of the sample with a Tukey follow-up test at a significance level of 5%. A multivariate Principal Component Analysis (PCA) analysis was carried out to map the physicochemical profile characteristics using the XLSTAT. The research results show that different types of sampling influence physicochemical properties such as protein, pH, and several color values, namely Lightness and Whiteness index. Based on the results of PCA analysis, it is known that dangke from Lombok is characterized by a low pH value with high protein, b*, Â°hue and chroma values. Meanwhile, dangke from Bima and Dompu have similar dangke physicochemical properties which are characterized by high Lightness, a* and whiteness index values. Meanwhile, Dangke from Sumbawa was not characterized by any parameters because its physicochemical characteristics were low. Overall, this study successfully mapped the differences in the characteristics of dangke based on its regional origins.